PENGUKURAN KINERJA PUSKESMAS BERDASARKAN KEPMENKES RI NO.828/MENKES/SK/IX/2008 DI KABUPATEN BOJONEGORO - SEPTI ATININGTYAS, DWI Septi (Jurnal Akuntansi AKUNESA, 2012)
The purpose of the study to finding out the measuring performance of Kalitidu, Padangan, and Wisma Indah Puskesmas if they are be compared to SPM appropriate with Kepmenkes RI No.828/MENKES/SK/IX/2008. This study used primer data and use comparative analysis to analyze the data that compare measuring performance of three puskesmas with SPM also compare each puskesmas. The result of this study show that there are some indicator of SPM in each puskesmas don’t appropriate with that standard. And the puskesmas that has the best measuring performance is Wisma Indah Puskesmas if that is seen from the result of service achievement.Keywords: Measuring Performance, SPM, Puskesmas